Mean spirit - Hogan, Linda (Ivy books., 1992)
"Early in this century, rivers of oil were found beneath Oklahoma land belonging to Indian people, and beautiful Grace Blanket became the richest person in the Territory. But she was murdered by the greed of white men, and the Graycloud family, who cared for her daughter, began dying mysteriously too. Letters begging for help sent to Washington, D.C., went unanswered, until at last a Native American government official, Stace Red Hawk, traveled west to investigate. What he found has been documented by history: rampant fraud, intimidation, and murder. But he also found something truly extraordinary--his deepest self and abiding love for his people, and their brave past."--Page 4 of cover.